Comparison of results in C1 paddling functional test and in arm crank ergometrics in canoe slalom elite athletes - Riha, M.; Busta, J.; Kovárová, L.; Bilý, M. (Studia Sportiva, 2018)
Background: Recently, there have been rising demands on the specifics of functional load testing, which should with its motor structure correspond or at least draw near the sport specialization. However, evaluation of specific forms of diagnostics is very pure in canoe slalom. Objective: The aim of the study was to compare a physiological response based on results in graded functional test when paddling in a single canoe (C1) and results reached in the standardized arm crank ergometrics.Methods: The research sample consisted of 6 elite Czech single canoeists, members of Czech senior national team and the Czech national team up to 23 years. Their average weight was 79.7±6.6 kg, height 183.4±6.6 cm and age 23.6±3.9 years.Results: When comparing the result values of physiological indicators measured in both functional tests, we have found out significant differences (statistical and substantive) in variables: VO2peak (p=0.00; 15.1%), VEpeak (p=0.06, 11.1%), HR (p=0.02; 5.7%), RR (p=0.18; 9.3%), VT (p=0.00; 18.8%) and RER (p=0.26; 4.0%). With the exception of respiratory rate, significantly lower values of all physiological variables were found in on-water testing (C1). Although there was a strong correlation between the VO2peak indicators (r=0.79, p=0.06) found between paddling and crank ergometrics, this relationship cannot be considered significant (p=0.06) due to the small research sample.Conclusions: To evaluate on-water testing and to determine the external validity of arm crank ergometrics for C1 diagnostics, it is necessary to test a bigger research sample. Therefore, it is a pilot study. However, the results indicate that the physiological load requirements in the C1 category are different from those of the kayak category (K1). Although C1 paddlers reached similar VO2peak values in the arm crank ergometrics as kayakers, in the on-water test they reached about 10 ml.kg.min-1 lower oxygen uptake compared to kayakers (Busta, Bílý, Suchý, & Kovárová, 2017).